Kajian Pengendalian Pemanfaatan Ruang Terhadap Alih Fungsi Perumahan (Studi Kasus Sungai Bambu, Jakarta Utara) - Keristian, Hari (Journal of Urban and Regional Development Studies, 2023)
The house has an important function and role in human life, because the house is a reflection and embodiment of the human person. Komarudin (1997:300) says that the house has three important meanings for human life, namely a place for shelter, fostering and family activities. The phenomenon of changes in residential land use is visible to the naked eye in Sungai Bambu Village, Tanjung Priok District, City of Adm. North Jakarta, there are many export-import trade and service offices that use the home utilization zone as an office. The location of the Sungai Bambu Village is adjacent to the Tanjung Priok port (Jakarta International Container Terminal/JICT), the pattern of existing land use is dominated by settlements and industry/warehousing. This study raises the aspect of spatial use control over changes in spatial use that occur, through licensing and non-licensing mechanism strategies that have been running in the first 7 years since the PZ RTRW and RDTR were enacted, whether they are effective or need to be improved.